2022
DOI: 10.3390/agriculture13010121
|View full text |Cite
|
Sign up to set email alerts
|

Response of Winter Wheat (Triticum aestivum L.) to Selected Biostimulants under Drought Conditions

Abstract: To prevent the staggering degradation of the environment, restrictions in the use of plant protection products and fertilizers are being strengthened every year. Therefore, methods for improving plant tolerance to unfavorable environmental conditions are sought to positively affect both plants and the natural environment. Here, we evaluated and compared the efficacy of four commercial biostimulants on the tolerance of winter wheat to drought stress. The effects of the following biological agents: Bacillus sp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Previous findings [68,69] showed that the concurrent inoculation of various microbial strains, along with organic amendment, can boost the performance of plants. Radzikowska-Kujawska et al [70] demonstrated that inoculation with PGPR considerably increased lettuce growth and resistance to abiotic stress due to its phosphate solubilizing capabilities. For instance, compared to the control, the C, R + C, and M + C treatments resulted in a considerable increase in the shoot biomass of lettuce plants of 160%, 120%, and 156%, respectively [71].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings [68,69] showed that the concurrent inoculation of various microbial strains, along with organic amendment, can boost the performance of plants. Radzikowska-Kujawska et al [70] demonstrated that inoculation with PGPR considerably increased lettuce growth and resistance to abiotic stress due to its phosphate solubilizing capabilities. For instance, compared to the control, the C, R + C, and M + C treatments resulted in a considerable increase in the shoot biomass of lettuce plants of 160%, 120%, and 156%, respectively [71].…”
Section: Discussionmentioning
confidence: 99%